Identifying the role of sociodemographic factors in major depressive disorder and suicidality among Spanish-speaking Latino patients in a federally qualified health center. Issue 5 (3rd September 2018) - Rogers, Andrew H.; Short, Nicole A.; Robles, Zuzuky; Bakhshaie, Jafar; Viana, Andres; Schmidt, Norman B.; Garza, Monica; Ochoa-Perez, Melissa; Lemaire, Chad; Bogiaizian, Daniel; Medvedeva, Angela; Zvolensky, Michael J.
Abstract: Rates of suicide and major depressive disorder (MDD) are currently at the highest point in the history of the United States (US). However, these rates are not distributed evenly among the population and Latinos show disproportionately high rates of both suicide and MDD. Yet, past research has infrequently explored factors related to suicide and MDD in primary care settings that serve as the major community portal for mental health among the Latino population. Thus, the current study investigated sociodemographic variables (marital status, nativity, education, employment, primary language, age, and gender) in terms of their relations with suicidal ideation, suicide risk, MDD, and MDD symptom severity among Latino primary care patients in a Federally Qualified Health Center ( N = 634, M age = 39.46, SD = 11.46, 87.1% female). Results indicated that gender and Nativity were associated with suicidal ideation, older age was associated with suicide risk, and higher education and having a partner were negatively associated with MDD and depressive symptom severity. These results provide novel insight into the role of sociodemographic factors predicting suicide and MDD among Latinos in primary care, and suggest greater scientific and clinical attention can be focused on certain sociodemographic factors to offset mental health disparities among this group.